Behavioural study of Asian golden cats in the night safari, Singapore. - Lee, Pei Shan. (2013)
As Asian Golden Cats in the wild are increasingly threatened by both poaching and deforestation, efforts have been made to breed them in captivity with varying success. Not much is currently known about these felids, yet information pertaining to them is essential to such breeding projects. Hence, studies such as this have been conducted to learn more about their activities within the captive environment, as well as about various factors that influence their behaviour. Conducted in the Night Safari, Singapore, this study focuses on identifying the above for a pair of captive Golden Cats, as well as the estrous cycle of the female. Data was collected using focal and scan sampling. The estrous period of the female lasted seven days, when rolling, interactions, and rubbing frequencies increased significantly. The amount of time the cats spent together also increased. The female Golden Cat exhibited an average of 29.82% activity during the observational timeframe. A negative correlation between humidity and activity levels was also observed. Differences in the felids’ responses towards enrichment were also noted. Although breeding was not successful during this observatory period, suggestions were made to increase the breeding potential of this pair and to aid in further studies.